Fatherhood - Logelin, Matthew (Grand Central Publishing, 2021)
Matt and Liz Logelin were high school sweethearts. After years of long-distance dating, the pair finally settled together in Los Angeles, and they had it all: a perfect marriage, a gorgeous new home, and a baby girl on the way. Liz's pregnancy was rocky, but they welcomed Madeline, beautiful and healthy, into the world. Just twenty-seven hours later, Liz suffered a pulmonary embolism and died instantly, without ever holding the daughter whose arrival she had so eagerly awaited. Though confronted with devastating grief and the responsibilities of a new and single father, Matt did not surrender to devastation; he chose to keep moving forward-to make a life for Maddy. In this memoir, Matt shares bittersweet and often humorous anecdotes of his courtship and marriage to Liz; of relying on his newborn daughter for the support that she unknowingly provided; and of the extraordinary online community of strangers who have become his friends. In honoring Liz's legacy, heartache has become solace.